Urinary IL-18 is associated with arterial stiffness in patients with type 2 diabetes - Caifeng Shi; Aiqin He; Xiaomei Wu; Lulu Wang; Xueting Zhu; Lei Jiang; Junwei Yang; Yang Zhou (Frontiers in Endocrinology, 2022)
ObjectiveDiabetic kidney disease (DKD) has been shown to be associated with an excess risk of cardiovascular death. Inflammation has been considered central to type 2 diabetes (T2D) pathophysiology, and inflammation markers have been linked to cardiovascular disease. The serum and urinary IL-18 levels were significantly elevated in patients with T2D; however, whether interleukin 18 (IL-18) are associated with the severity of arterial stiffness remains to be determined. This study examined the relationship of IL-18 levels with pulse wave velocity (PWV) as a reflector for arterial stiffness in patients with T2D.MethodsA total of 180 participants with T2D who had undergone PWV examination were enrolled. Serum and urinary IL-18 levels were measured using sandwich enzyme linked immunosorbent assay (ELISA) kits. Arterial stiffness was determined by carotid–femoral PWV (cf-PWV) and carotid–radial PWV (cr-PWV).ResultsThe urinary IL-18 levels correlated positively with cf-PWV in patients with T2D with DKD (r = 0.418, p < 0.001); however, we found no significant correlation between urinary IL-18 and cf-PWV in diabetic subjects without DKD. In addition, we found no significant correlation between urinary IL-18 and cr-PWV in participants with T2D with or without DKD. Moreover, the association remained significant when controlling for arterial stiffness risk factors, urinary albumin-to-creatinine ratio and estimated glomerular filtration rate. cf-PWV was greater in the higher group of urinary IL-18 than in the lower group. Nevertheless, we found no significant correlation between serum IL-18 and cf-PWV in participants with T2D.ConclusionThe urinary IL-18 levels appear to be associated with greater cf-PWV, suggesting the link between urinary IL-18 and arterial stiffness in patients with T2D.